An Alternative Theoritical Framework of Diversity in Educational Sciences - Dezső, Renáta Anna (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The present contribution offers a theoretical introduction to concepts rarely known and realized in Hungarian educational sciences and teacher education. As a consequence of neurodiversity we may tolerate the value of subjective differences and consider alternative types of learning described by plural intelligence concepts. This study focuses on three of these theories: Gardner’s multiple intelligences (MI) theory, Sternberg’s triarchic model and Dweck’s mindset theory – concerning their possible educational consequences. The author’s intention is to contribute to the recognition of these ideas in the circles of the Hungarian speaking professional audience in the Carpatian Basin. The research was realized in the frames of TÁMOP 4.2.4. A/2-11-1-2012-0001 “National Excellence Program – Elaborating and operating an inland researcher personal support system.” The project was subsidized by the European Union and co-financed by the European Social Fund.